The effect of cyber-risk insurance to social welfare - Kuru, D.; Bayraktar, S. (Emerald Group Publishing Ltd., 2017)
Purpose - Previous studies generally focused on the definition of cybercrime and its effect on the market. Following Kesan's study, this paper aims to analyse the relationship between cyber insurance and social welfare and compare it among three countries, namely, USA, UK and Turkey. The paper also discusses the main obstacles that the cyber insurer has to deal with and its effect on social welfare. This paper answers two questions related to cyber insurance at an aggregate level. First, "what kind of contribution does cyber insurance make to social welfare?" Second,"What kind of problems do insurers and insured have to face?" Although the findings are similar to Kesan's study, this study gives an opportunity to make a country-based study and interpret the results with a different perspective. Design/methodology/approach - The calculation of utility is also important for interpreting social welfare in the market. Consumer behaviour under uncertainty constructs the background for this paper because the risks of malicious attacks are contingent and independent, which means that consumers have to make their decisions under uncertainty. Von-Neumann-Morgenstern utility function is used for interpreting consumer's behaviour. Findings - Basically, there are two important conclusions that can derive for cyber insurance. First, cyber insurance can be defined as a higher security investment when coupled with increased levels of safety and a robust IT infrastructure. Second, cyber insurance, as a high-security investment, would have a positive impact on social welfare by making the internet safer for all users. The results show that the problems that lead to market failure can be virtually eliminated with an accurate risk assessment that leads to appropriate premium levels for insured. These results are consistent with those of study by Kesan et al. (2006). Research limitations/implications - Data availability for different industries have limited the ability to compare the impact of cyber-crime to different sectors. Originality/value - Technological devices have become part of our daily life. Although they have brought us increasing access to all types of information, including opportunities for business, they have also increased the risk of malicious attacks and the risk of e-crime. By replicating the economic model used by Kesan et al. (2006), social welfare losses and insurance premiums are calculated for three countries: USA, UK and Turkey. Questions pertaining to contribution of cyber insurance to social welfare and problems faced by insurers and insured are addressed. © Emerald Publishing Limited.
Keywords: Cyber Risk; Cyber Risk İnsurance; Social Welfare